Analysis of the Influence of Land Use Change on the Spatial-Temporal Variation of Water Yield - CHEN Xuanxuan; WANG Lina (Renmin Zhujiang)
Water yield is one of the important service functions of the urban ecosystem,and land use change has a certain influence on regional water yield change.Therefore,it is of great significance to analyze the correlation between water yield and land use change.With Guangdong Province as the research object,the influence of land use change on water yield was explored by comprehensively applying tools such as InVEST,ArcGIS,and SPSS.The results showed that from 1980 to 2020,the variation range of the average water yield depth in the whole province was 974~1 375 mm.Spatially,it showed the spatial distribution characteristics of higher water yield in the central cities of Guangdong Province and lower water yield in the northeast and southwest.The increase in urban and rural land areas had a certain positive correlation with the increase in water yield.The increase in the area of cultivated land,forest land,grassland,and water area had a certain negative correlation with the water yield.